A challenging case of cutaneous leishmaniasis with thrombophlebitic complication - Antoine Willemart; Laura Mengeot; Jean‐Cyr Yombi; Léo Paul Secco; Marie Baeck (Wiley, 2023)
Abstract We report a case of cutaneous leishmaniasis caused by Leishmania guyanensis with sporotrichoid lymphocutaneous dissemination of the parasite and thrombophlebitic complication in a 32‐year‐old man who had recently travelled to French Guiana. After initial failure of empirical treatment with amphotericin B, the patient evolved favourably on high doses of intramuscular injections of meglumine antimoniate for 2 months. This case illustrates the existence of lymphocutaneous forms and possible thrombophlebitic complications of leishmaniasis. It also highlights the challenges in the management of leishmaniasis, despite the existence of guidelines and a wide therapeutic arsenal.